Students’ Critical Thinking in Solving Statistical Problems Collaboratively - Mufidah, Latifah Nuryah Rachma; Khoiriyah, Siti (Journal of Mathematical Pedagogy (JoMP), 2021)
Critical thinking and collaborative is an ability that is needed by students in 21st century education. The purpose of this research is to describe students' critical thinking skills in solving statistical problems collaboratively. The type of research used in this study is descriptive research with a qualitative approach. The subjects of this study were 4 grade 11 students of SMA Negeri in Mojokerto where students would work in pairs or collaborate with 2 people to solve statistical problem-solving questions. The research methods used are critical thinking skills tests in collaborative statistical problem solving and interviews. The results obtained from this study showed that students' critical thinking skills in solving statistical problems collaboratively were divided into two categories, namely high and low. Subjects who have a high critical thinking ability category are able to fulfill the indicators of interpretation, analysis, and inference. Collaboration ability in solving problems goes well. Collaboration exchanges information and gives advice to each other in solving the given problem. Subjects who have low critical thinking ability category are less able to interpret the problem, and fulfill the indicators of analvsis and inference. Collaboration ability in solving problems is less.